Planning of Gosong Pasir Beacon Buoy with Flush-Mounted Aluminum Anode as a Corrosion Solution for SBNP - Sumargo Sumargo; Fauzaniah Hijjatul Jensi Nun; Siti Muthmainnah Az Zahra (Eduvest - Journal of Universal Studies, 2025)
Based on Law No.43 of 2008, guarding and monitoring the coastline of Indonesia is very important, because it is closely related to the boundaries of the sea area that needs to be regulated for national defense. In the sea area, Navigational Aids (SBNP) type of beacon signs are used as a sign of state boundaries which have been regulated in Permenhub No.25 of 2011. In Indonesia, the beacon building in the waters of Gosong Pasir, Riau Province, experienced two collapses within 12 years. Therefore, this study examines more deeply and provides solutions to structural strength, cathodic protection, and mechanical electrical structures. The data used in this study are bathymetry data, underwater image data, sub bottom profile data, tide data, current data, and sediment sample data. Hydrodynamic modeling is carried out to obtain platform elevation and cycle time results. Furthermore, for corrosion problems, ASTM A252 Grade B and ASTM A53 Grade B steel pipes are proposed with Flush-Mounted Aluminum Anode cathodic protection with a trapezoidal cross section and coating process.